(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
During the second Balkan war, Serbian military invaded the valley of river Bregalnica. After the military actions ended and the Bucharest agreement was signed in 1913, the Stip district was formed. The administrative center was located in the city of Stip. The district was composed of six provinces: Štip, Kočani, Maleševo, Radoviš, Sv.Nikole and Carevo Selo area. Up until 1912 the territory where Serbian authorities will form the Stip district was part of the Skopje sanxak, precisely part of the Kosovo vilajet. In January 1914 the Stip district was renamed into Bregalnica district. According to the official census data in 1913 there were 101.442 residents living in Bregalnica district, which is a significantly decreased number of the total population compared to the period right before the Balkan wars. The main reason for this decrease of population was the emigration of the Turkish, the Muslim population after 1912. The fall of 1915 there was Bulgarian administration established in Vardar Macedonia. The Ministry of Interior and people’s health of Bulgaria in 1917 published a brochure with the title “List of populated places in Macedonia, Morava ad Odrin area ”. According these data to the Stip district also added were the Kavadarci and Negotino provinces. The total population of the district in 1917 was 138.430 residents. In order to better compare the data from the previous years, if we take out the number of residents in the mentioned Kavadarci and Negotino district, which is 36.204 habitants, in the Stip district there were 102.228 citizens living. After the establishment of the power of Kingdom SHS, the first census was conducted in 1921. According to these data, in the Bregalnica district, which kept its borders from 1913, there were 104.347 citizens living. The published data from the census in 1921, being so detailed, help in the comparison analyzing of the structure of the population on the territory of Macedonia which was under the power of KSHS regarding the period from the last decade from the Ottoman ruling, as well as during the Balkan wars and the First World War.